Effect of dietary supplementation of ghee residue on serum biochemistry and haematology of Japanese quails - S. Umamaheshwari; S.T. Selvan; P.Muthusamy; L. Radhakrishnan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Consumer preference towards diversified poultry meat is increasing steadily because of increased health consciousness of consumers. Among the diversified poultry, Japanese quails are the main contributors and its meat is a “gourmet’s delight” due to its good quality animal protein. The ingredients like maize, soyabean meal, fish meal and vegetable oils constitutes a major source of energy, protein and fat in the poultry feed. Poultry farmers are facing deep crisis due to unprecedented increase in the price of these essential feed ingredients. Feed cost is the major expenditure involved in the poultry production and constitutes around 60-70% of the total cost, Hence, a judicious use of ingredients, utilizing industrial by-products/wastes to reduce the cost of production on one side and maximizing the nutrient utilization in poultry on the other side is the need of the hour.